The COVID-19 pandemic and the economy in Southern Africa - Neva Seidman Makgetla (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The COVID-19 pandemic has had severe economic consequences in Southern Africa, resulting in an unprecedented decline in production and employment. Similar policy responses have emerged across the region, centred on temporary and inadequate relief for workers and businesses; very limited fiscal and monetary stimulus efforts; and vague and under-resourced commitments to accelerate industrialization and infrastructure investment. Responses to the pandemic recession have underscored the region's limited power on global financial markets, which has constrained both relief programmes and fiscal policy. Moreover, limited manufacturing capacity in most countries has meant that increased infrastructure and industry investment could just fuel imports. Limited policy responses have also reflected the depth of inequality in Southern Africa. Both businesses and policy-makers could largely protect themselves from the pandemic's economic and health impacts. That made them less likely to act urgently or decisively to address the consequences for less-privileged groups.
Keywords: N17; N57; O23; Q34; 330; Southern Africa; case studies; COVID-19; economic policy; development policy